Emerging Flora In Gradient Of Mining Post Succession In Condoto, Chocó - Valoyes Cardozo, Zulmary; Ramírez Moreno, Giovanny (Universidad Pedagógica y Tecnológica de Colombia, 2020)
A comparative analysis of the plant community was made in three areas affected by mining and a control forest in Jigualito (Condoto). To determine changes in the composition and structure of the vegetation, we selected three abandoned mines with time periods of 5, 15 and 30 years and a forest without mining history. In each area 5 plots of 5 x 20 were installed, equivalent to 500m², the vegetation present in each selected area was recorded and measured. In abandoned mines, the distribution of wealth, composition and structure of the plant community is conditioned by the chronology of mining abandonment and the evolution of succession levels, evidencing the increase in wealth and the decrease in abundance as temporality increased of cessation of activity, favoring the increase of diversity and the appearance of a more complex structure. Therefore it can be inferred that, after 3 decades, the plant community is in approximately less than 50% of its initial conditions in numerical terms of composition, however, the floristic arrangement is completely different from that of the control forest, therefore , the mining activity causes a series of areas with different floristic arrangements.